Age distribution of dengue cases in southern Vietnam from 2000 to 2015. - Anne-Frieda Taurel; Chan Quang Luong; Thi Thanh Thao Nguyen; Kien Quoc Do; Thanh Hai Diep; Thanh Vu Nguyen; Minh Thang Cao; Thi Nhu Dao Hoang; Phuong Thao Huynh; Thi Kim Loan Huynh; Minh Hieu Le; Joshua Nealon; et al. (Public Library of Science (PLoS), 2023)
Background Dengue is the most common vector-borne viral infection. In recent times, an increase in the age of cases with clinical dengue has been reported in the national surveillance system and published literature of Vietnam. This change not only alter the risk of transmission and disease burden in different populations but also will impact for prevention and control strategies. A retrospective study was conducted from 2000 to 2015 in 19 provinces of southern Vietnam to describe the changes in age distribution of dengue cases and circulating serotypes. Methodology/principal findings The study is a time trend analysis of the data aggregated from the database of dengue surveillance system. The database consisted of clinically diagnosed and laboratory-confirmed cases of dengue in southern Vietnam from 2000 to 2015. In the study period, the mean age of dengue cases increased from 12.2 ± 8.8 years old (y/o) to 16.8 ± 13.3 y/o between 2000 and 2015. Majority of severe cases were observed in the age group of 5-9 y/o and 10-14 y/o. Overall, the mortality and case fatality rates (CFR) were lowest during 2010 to 2015, and all four serotypes of dengue were observed. Conclusions/significance With the exception of severe form, the age distribution of clinical cases of dengue appears to be shifting towards older age groups. An increase in the mean age of clinical cases of dengue has been observed in southern Vietnam over the past decade, and the highest incidence was observed in age group of 5-14 y/o. All serotypes of dengue were in circulation.